OS X Mavericks - Beighley, Lynn (Peachpit Press, 2014)
If you are new to OS X, you'll learn the basics of how to use OS X efficiently and joyfully. From there, you can move on to customize Mavericks to suit the way you work. And if you've been using OS X already, you'll learn how to get the most out of iCloud integration, Notifications, Maps, iBooks, Finder tabs, multiple displays, and more.
Print version record
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer) -- Programming; Systèmes d'exploitation (Ordinateurs); Macintosh (Ordinateur); Programmation; operating systems; Macintosh (Computer); Programming